1963
DOI: 10.1001/archpedi.1963.02080040366007
|View full text |Cite
|
Sign up to set email alerts
|

Parathyroid Hyperplasia in an Infant

Abstract: Diffuse hyperplasia of the parathyroid glands is a rare condition in infancy, and both the clinical picture and the histologic structure of the parathyroid glands differ somewhat from those of the comparable disorder in adults. As far as we can ascertain, two previous fatal cases1,2 have been reported with both clinical and postmortem descriptions. In addition, a probable further example of this condition, with apparently successful surgical intervention, has been reported by Landon.3 In these three cases the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1966
1966
1997
1997

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Some cases in neonates are referred to in the section dealing with familial hyperparathyroidism. Randall and Lanchlon (1963) reported the case of an infant with diffuse hyperplasia of the parathyroid glands, and having a clinical and histological picture which differed somewhat from that usually seen in children. The child, who was mentally retarded, deaf, and dumb, and was admitted to hospital soon after birth, was miserable and underweight.…”
Section: Hyperparathyroidism In Childrenmentioning
confidence: 91%
“…Some cases in neonates are referred to in the section dealing with familial hyperparathyroidism. Randall and Lanchlon (1963) reported the case of an infant with diffuse hyperplasia of the parathyroid glands, and having a clinical and histological picture which differed somewhat from that usually seen in children. The child, who was mentally retarded, deaf, and dumb, and was admitted to hospital soon after birth, was miserable and underweight.…”
Section: Hyperparathyroidism In Childrenmentioning
confidence: 91%
“…Marx et al suggested in 1982 that some cases of NHPT might be the homozygous form of FBHH, because children with NHPT were encountered in families with both parents affected by FBHH (3). However, NHPT has also been noted in cases where only one parent had clinically apparent FBHH (3,7,(14)(15)(16)(17)(18), and many further cases of NHPT appear to be sporadic, with both parents being normocalcemic (1,(19)(20)(21)(22)(23)(24)(25)(26). Thus the nature of the genetic defect and how it produces two different hypercalcemic syndromes was obscure.…”
Section: Introductionmentioning
confidence: 99%
“…Primary hyperparathyroidism in childhood (PHPC) may be encountered both in infants and children, but the disease seems most frequent in the pre-adolescent and adolescent age group. Including some doubtful cases, 12 of the reported patients are infants (1,4,6,7,14,18,19,20), 2 of these were brothers with symptoms starting in the neonatal period (9). PHPC is more common among males than females (ratio 3 : 2).…”
mentioning
confidence: 99%